2020
DOI: 10.1371/journal.pgen.1009046
|View full text |Cite
|
Sign up to set email alerts
|

The Ccr4-Not complex regulates TORC1 signaling and mitochondrial metabolism by promoting vacuole V-ATPase activity

Abstract: The Ccr4-Not complex functions as an effector of multiple signaling pathways that control gene transcription and mRNA turnover. Consequently, Ccr4-Not contributes to a diverse array of processes, which includes a significant role in cell metabolism. Yet a mechanistic understanding of how it contributes to metabolism is lacking. Herein, we provide evidence that Ccr4-Not activates nutrient signaling through the essential target of rapamycin complex 1 (TORC1) pathway. Ccr4-Not disruption reduces global TORC1 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 95 publications
(147 reference statements)
0
10
0
Order By: Relevance
“…For instance, CCC1 overexpression could cause a decrease in vacuolar lumen acidification, since Ccc1 seems to be a H + /Fe 2+ antiporter [12]. In this sense, recent data demonstrated that the loss of vacuolar acidification leads to oxidative damage of mitochondrial Fe/S cluster biosynthesis components and activities and the development of an age-related mitochondrial dysfunction [39,40]. Importantly, Ccc1 overexpression toxicity was not observed in high iron media (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 89%
“…For instance, CCC1 overexpression could cause a decrease in vacuolar lumen acidification, since Ccc1 seems to be a H + /Fe 2+ antiporter [12]. In this sense, recent data demonstrated that the loss of vacuolar acidification leads to oxidative damage of mitochondrial Fe/S cluster biosynthesis components and activities and the development of an age-related mitochondrial dysfunction [39,40]. Importantly, Ccc1 overexpression toxicity was not observed in high iron media (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 89%
“…Genetic approaches have identified some Ccr4-Not mutants as being rapamycin-sensitive, which indicates the relation between this complex and the TOR pathway [ 56 , 57 ]. In fact, Ccr4-Not may act upstream of TOR through a mechanism that involves V-ATPase [ 58 ]. Ccr4-Not associates with both RNA pol I and rDNA, which indicates a role in RNA pol I regulation [ 59 ].…”
Section: Rna Pol I Transcriptional Activity Is Regulated By the Tor P...mentioning
confidence: 99%
“…Additional Not4 studies have revealed that it controls translation (23)(24)(25), proteostasis (26)(27)(28), and endolysosomal-dependent nutrient signaling (29), but its role in these processes remains incompletely understood. Specifically, Not4 monoubiquitinates both the ribosomal protein Rps7a and the Egd1 and Egd2 (Egd1/2) subunits that make up the nascent polypeptide associated complex (NAC) involved in co-translational quality control (23,25).…”
Section: Introductionmentioning
confidence: 99%
“…Macroautophagy regulates protein quality control so Ccr4-Not, and specifically Not4, may contribute to nutrient stress responses and protein quality control through macroautophagy regulation. Ccr4-Not also activates nutrient signaling through the TORC1 pathway by promoting the function of the vacuole V-ATPase H + pump that both acidifies the vacuole and activates TORC1 and PKA signaling in response to nutrients (29,(35)(36)(37). Ccr4-Not mutants exhibit synthetic sick or lethal genetic interactions with endolysosomal pathway effectors, including V-ATPase mutants and vacuolar protein sorting (Vps factors) (8,(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation